Isolation, identification and antimicrobial susceptibility of the bacteria isolated from Hyalomma dromedarii infesting camels in Al-Jouf province, Saudi Arabia - Aljasham, Alanoud T.; Damra, Eman M.; Alkahtani, Nora S.; Alouffi, Abdulaziz; Al Salem, Waleed S.; Alshabanah, Aljoharah O.; Alotaibi, Moureq; Tanaka, Tetsuya; Ali, Abid; Almutairi, Mashal M. (Frontiers in Veterinary Science, 2023)
Ticks are important ectoparasites that transmit various pathogens causing morbidity and mortality in humans and animals. Saudi Arabia faces several challenges that can contribute to the emergence and spread of antimicrobial resistance (AMR) bacteria. These challenges require collaborative efforts to successfully achieve significant control of AMR in the country. The present study aims to isolate bacteria from camels' tick Hyalomma dromedarii in Al-Jouf province to identify and determine these isolates' antimicrobial susceptibilities. Forty-nine ticks were collected from dromedary camels and morphologically classified as H. dromedarii. Ticks were then homogenized and plated individually, which resulted in the isolation of 55 bacteria. The results showed that the bacterial isolates belong to 20 different species. About 71% (n = 39) of the total isolates were identified as Gram-positive bacteria comprised of 11 different species, while 29% (n = 16) of the total isolates were Gram-negative bacteria comprised of 9 different species. The most prevalent isolate within the total samples was Staphylococcus lentus (22.45%, 11/49), followed by Staphylococcus pseudintermedius (18.37%, 9/49) and Sphingomonas paucimobilis (16.33% 8/49). The antimicrobial susceptibility profile of Gram-positive bacteria showed that 100% (n = 31) were resistant to benzylpenicillin; 90.3% (n = 28) were resistant to oxacillin; 58.1% (n = 18) were resistant to clindamycin; 48.4% (n = 15) were resistant to vancomycin. In addition, 32.3% (n = 10) were resistant to trimethoprim/sulfamethoxazole and rifampicin; 25.8% (n = 8) were resistant to erythromycin; 16.1% (n = 5) were resistant to teicoplanin; 6.5% (n = 2) were resistant to tetracycline. All Gram-positive bacteria were 100% susceptible to linezolid, gentamicin, tobramycin, levofloxacin, moxifloxacin, tigecycline, and nitrofurantoin. In antimicrobial susceptibility tests for the Gram-negative bacteria, 57.14% (n = 8) of the identified bacteria were resistant to ampicillin, whereas 50% (n = 7) were resistant to cefoxitin and ceftazidime. About 28.57% (n = 4) of the Gram-negative bacteria were resistant to ceftriaxone, trimethoprim/sulfamethoxazole. In addition, 21.43% (n = 3) were resistant to amoxicillin/clavulanic acid and cephalothin; 14.29% (n = 2) were resistant to cefepime and nitrofurantoin; 7.14% (n = 1) were resistant to piperacillin/tazobactam and tigecycline. However, all Gram-negative bacteria were susceptible to other examined antimicrobials. This is the first study that investigates the role of the hard tick as a potential reservoir for AMR pathogens within our region.